Familial hyperchlolesterolaemia: a monogenic cause of early CHD - Humphries, Steve (Henry Stewart Talks, 2008)
Clinical diagnostic criteria, Prevalence in UK, Effects of statins on cholesterol and CHD risk lowering, The 3 genes where mutations cause FH (LDLR, APOB, PCSK9), Clinical Genetics Diagnostic service for FH and examples in families, Cascade testing for FH patients using LDL cholesterol levels, The Overlap problem, The Simon Broome FH register project and the high risk of early CHD in those with an LDLR and PCSK9 mutation, The LDLR mutation database, Ethical issues about genetic testing for FH, Clinical questions in the management of FH, FH testing and insurance
Archived at 2023/08/31